2018
DOI: 10.1111/gcb.14330
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic capacity and leaf nitrogen decline along a controlled climate gradient in provenances of two widely distributed Eucalyptus species

Abstract: Climate is an important factor limiting tree distributions and adaptation to different thermal environments may influence how tree populations respond to climate warming. Given the current rate of warming, it has been hypothesized that tree populations in warmer, more thermally stable climates may have limited capacity to respond physiologically to warming compared to populations from cooler, more seasonal climates. We determined in a controlled environment how several provenances of widely distributed Eucalyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 123 publications
9
64
5
1
Order By: Relevance
“…Respiration and photosynthesis may acclimate to temperature together such that their ratio ( R/A ) is constant. This is consistent with some measurements of an invariant R/A ratio across a wide range of temperatures, but with some additional variation at exceptionally high or low temperatures (Atkin et al ., ; Aspinwall et al ., ; Slot & Winter, ; Crous et al ., ; Dusenge et al ., ). Importantly, several studies indicated that the R/A ratio changed in response to a change in growth temperature, but that a homeostatic R/A ratio was restored following the development of new leaves (Ziska & Bunce, ; Loveys et al ., ; Campbell et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Respiration and photosynthesis may acclimate to temperature together such that their ratio ( R/A ) is constant. This is consistent with some measurements of an invariant R/A ratio across a wide range of temperatures, but with some additional variation at exceptionally high or low temperatures (Atkin et al ., ; Aspinwall et al ., ; Slot & Winter, ; Crous et al ., ; Dusenge et al ., ). Importantly, several studies indicated that the R/A ratio changed in response to a change in growth temperature, but that a homeostatic R/A ratio was restored following the development of new leaves (Ziska & Bunce, ; Loveys et al ., ; Campbell et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The second important mechanism for acclimation was a change in the magnitude of JV r , as has also been observed by others (Kattge & Knorr, ; Crous et al ., , ; Lin et al ., ). The ratio determines the transition between the two limiting steps, W c and W j .…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence points to an increase in the frequency and intensity of HWs, which have affected more than 73% of the global terrestrial area since the mid-20th century (IPCC, 2013;Perkins-Kirkpatrick et al, 2016) and have caused large and widespread impacts at all ecological scales from the species level to the ecosystem level. Severe HW events not only rapidly reduce plant photosynthesis and respiration (Crous Kristine et al, 2018), decrease aboveground and belowground biomass accumulation (Qu, Chen, Dong, & Shao, 2018), and alter the (re)allocation of carbon and nitrogen within a plant (Li et al, 2017), but also result in a decrease in ecosystem gross primary productivity and net ecosystem carbon exchange (Ciais et al, 2005;Qu et al, 2018;Tatarinov et al, 2016).…”
Section: Introductionmentioning
confidence: 99%